The Impact of Uncertainty and Macroeconomic on Income Inequality in Indonesia - Williya Meta; Meilisa Meilisa; Lathif Arafat (Universitas Bangka Belitung, 2024)
This study explores the impact of global uncertainty and macroeconomic factors on income inequality in Indonesia from 1991 to 2023, employing the Autoregressive Distributed Lag (ARDL) and Error Correction Model (ECM) methodologies. The findings reveal that global uncertainty significantly reduces income inequality in the long term, while key macroeconomic variables like unemployment and real income have pronounced effects on inequality in both the short and long term. Unemployment is positively associated with income inequality, exacerbating the disparity as job losses primarily affect the lower-income segments. Real income increases, on the other hand, paradoxically heighten inequality due to the uneven distribution of wealth across socio-economic groups. Inflation, however, was found to have no significant effect on income inequality. The study highlights the role of economic policy uncertainty, which disproportionately affects the wealthier segments during economic downturns, leading to a relative decline in inequality. However, the persistent concentration of wealth among the top 10% underscores the need for policy interventions, including progressive taxation and social assistance programs. Policymakers are urged to address unemployment and ensure equitable income growth to mitigate inequality effectively. The research underscores the necessity of robust strategies to navigate global uncertainties and stabilize macroeconomic conditions to achieve inclusive growth in Indonesia.